MODELLING OF MITIGATING DIARRHOEA IN THE WETLAND AREA OF BANYUASIN DISTRICT, INDONESIA: A CROSS-SECTIONAL STUDY - Hermansyah; Muhammad, Irfannuddin; novrikasari, novrikasari; Muhammad, Hakim (Malaysian Journal of Public Health Medicine, 2021)
Diarrhoea is one of the causes of high morbidity and mortality rates in developing countries that have poor environmental sanitation, inadequate water supply, high poverty rates and low levels of education. The purpose of this study was to examine diarrhoea control models in toddlers of Banyuasin District wetlands. This study used a cross-sectional study design. The study was conducted in the wetland area of Banyuasin District with a sample of 296 respondents. Data analysis was performed in univariate, bivariate and multivariate. The results showed that there was a correlation between chemical indicators (p-value = 0.035), latrine sanitation (p-value = 0.004), latrine quality (p-value = 0.005), income (p-value = 0.023), and hand washing with soap (p-value = 0.035) with the occurrence of diarrhoea in toddlers of Banyuasin District wetlands area. 51.9% of diarrhoea prevention can be explained by the water factor (19.7%), sanitation factor (15.6%), personal hygiene factor (8.2%), toddler factor (4.8%) and mother factor (3.5%) in this study. Improvements of environmental sanitation related to healthy latrines, rubbish bins, sewerage and clean / drinking water sources, as well as intensive education about personal hygiene and breastfeeding toddlers can contribute in reducing the occurrence of diarrhoea in toddlers.